2007
DOI: 10.1111/j.1742-4658.2007.05854.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of cell‐free‐produced human endothelin B receptor reveals transmembrane segment 1 as an essential area for ET‐1 binding and homodimer formation

Abstract: The functional and structural characterization of G-protein-coupled receptors (GPCRs) still suffers from tremendous difficulties during sample preparation. Cell-free expression has recently emerged as a promising alternative approach for the synthesis of polytopic integral membrane proteins and, in particular, for the production of G-protein-coupled receptors. We have now analyzed the quality and functional folding of cell-free produced human endothelin type B receptor samples as an example of the rhodopsin-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 55 publications
0
45
0
Order By: Relevance
“…Another alternative involves bacterial expression of fusion proteins with the membrane-integrating protein mistic: preliminary data have suggested that it may facilitate the folding and insertion of eukaryotic proteins in bacterial hosts (Roosild et al, 2005). Finally, cell-free expression systems have been shown to support the production of milligram quantities of solubilized, functional IMPs (Liguori et al, 2007), particularly for GPCRs, in which ligand binding and structural homogeneity could readily be demonstrated (Ishihara et al, 2005;Klammt et al, 2007).…”
Section: Alternative Expression Systemsmentioning
confidence: 98%
“…Another alternative involves bacterial expression of fusion proteins with the membrane-integrating protein mistic: preliminary data have suggested that it may facilitate the folding and insertion of eukaryotic proteins in bacterial hosts (Roosild et al, 2005). Finally, cell-free expression systems have been shown to support the production of milligram quantities of solubilized, functional IMPs (Liguori et al, 2007), particularly for GPCRs, in which ligand binding and structural homogeneity could readily be demonstrated (Ishihara et al, 2005;Klammt et al, 2007).…”
Section: Alternative Expression Systemsmentioning
confidence: 98%
“…Recent advances in the expression and purification of membrane proteins have been described for various expression hosts, for example: Escherichia coli (Drew et al 2003(Drew et al , 2005Grisshammer et al 2005), yeast (Wedekind et al 2006;Lee et al 2007), insect cells (Massotte 2003), mammalian cells (Yin et al 2005;Werner et al 2008) and cell-free systems (Klammt et al 2007). However, from approximately 1000 known GPCRs, only five high-resolution 3-D structures of two distinct receptor types have been reported: bovine rhodopsin (Palczewski et al 2000) and opsin (Park et al 2008), squid rhodopsin (Murakami and Kouyama 2008), the human b2-adrenergic receptor Rosenbaum et al 2007) and the turkey b1-adrenergic receptor (Warne et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ETBR can form a homodimer (20,21). In this case, the homodimer shows a size of 100 kDa, and polymerization of the homodimer or a combination of the homodimer and other membrane proteins can show a size exceeding 200 kDa.…”
Section: Discussionmentioning
confidence: 97%